Social Determinants of Health: Underreported Heterogeneity in Systematic Reviews of Caregiver Interventions. (14th February 2020) - Young, Heather M; Bell, Janice F; Whitney, Robin L; Ridberg, Ronit A; Reed, Sarah C; Vitaliano, Peter P
Abstract: Background and Objectives: Although most people have some experience as caregivers, the nature and context of care are highly variable. Caregiving, socioeconomic factors, and health are all interrelated. For these reasons, caregiver interventions must consider these factors. This review examines the degree to which caregiver intervention research has reported and considered social determinants of health. Research Design and Methods: We examined published systematic reviews and meta-analyses of interventions for older adults with age-related chronic conditions using the PRISMA and AMSTAR 2 checklists. From 2, 707 papers meeting search criteria, we identified 197 potentially relevant systematic reviews, and selected 33 for the final analysis. Results: We found scant information on the inclusion of social determinants; the papers lacked specificity regarding race/ethnicity, gender, sexual identity, socioeconomic status, and geographic location. The majority of studies focused on dementia, with other conditions common in later life vastly underrepresented. Discussion and Implications: Significant gaps in evidence persist, particularly for interventions targeting diverse conditions and populations. To advance health equity and improve the effectiveness of interventions, research should address caregiver heterogeneity and improve assessment, support, and instruction for diverse populations. Research must identify aspects of heterogeneity that matter in intervention design, while recognizing opportunities for common elements and strategies.